1982
DOI: 10.1111/j.1471-4159.1982.tb04709.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of the S‐100 Protein Specific Binding Sites in Synaptosomal Particulate Fractions and Subfractions

Abstract: The specific interaction of S-100 protein with synaptosomal particulate fractions (SYN) was further investigated with special reference to the number of binding components and their localization in synaptosomal subfractions. Binding studies were conducted on SYN from various CNS regions, on synaptosomal subfractions from the cerebral cortex, and on cerebral cortex SYN under various conditions. The results suggest that S-100 binds to two populations of membrane sites: high -affinity sites, which seem to be conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1982
1982
1986
1986

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The results (not shown) indicated that the protein bound in the presence'of KC1 completely dissociated in approximately 5 min after any association time, and to the same extent whether or not an excess of unlabeled S-100 was present in the dissociation medium; in addition, protein bound to phospholipase C-or D-treated SYN dissociated to a much greater extent than that bound to untreated SYN, both in the absence and presence of unlabeled s-100. Together, these data indicate that S-100 forms a tight complex with high-affinity sites and confirm that S-100 must be in its Caz+ conformation (Calissano et al, 1976) for high-affinity binding to occur (Donato, 1982).…”
Section: Resultssupporting
confidence: 53%
See 4 more Smart Citations
“…The results (not shown) indicated that the protein bound in the presence'of KC1 completely dissociated in approximately 5 min after any association time, and to the same extent whether or not an excess of unlabeled S-100 was present in the dissociation medium; in addition, protein bound to phospholipase C-or D-treated SYN dissociated to a much greater extent than that bound to untreated SYN, both in the absence and presence of unlabeled s-100. Together, these data indicate that S-100 forms a tight complex with high-affinity sites and confirm that S-100 must be in its Caz+ conformation (Calissano et al, 1976) for high-affinity binding to occur (Donato, 1982).…”
Section: Resultssupporting
confidence: 53%
“…Dissociation experiments were also conducted after incubation of 12sI-labeled S-100 with SYN in the presence of 0.2M KCI or with SYN pretreated with either phospholipase C (EC 3.1.4.3) or D (EC 3.1.4.4). Under all these conditions high-affinity S-100 binding appeared to be abolished (Donato, 1982). The results (not shown) indicated that the protein bound in the presence'of KC1 completely dissociated in approximately 5 min after any association time, and to the same extent whether or not an excess of unlabeled S-100 was present in the dissociation medium; in addition, protein bound to phospholipase C-or D-treated SYN dissociated to a much greater extent than that bound to untreated SYN, both in the absence and presence of unlabeled s-100.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations